Toward a learning-to-performance program for interprofessional long-term care teams: Team Essentials to foster engagement, reciprocity, and meaningful, sustained practice change. Issue 2 (3rd April 2021) - Meyer, Raquel M.; Reguindin, Jennifer; Helfenbaum, Shoshana; Boutcher, Faith; Tsui, Joyce; Tafler, Melissa; Kelson, Elizabeth; Conn, David
ABSTRACT: This paper presents the design, delivery, and preliminary evaluation of a gerontological learning-to-performance program. An interprofessional educational team sought to integrate leading clinical and educational practices into Team Essentials to engage long-term care teams in learning to improve performance. Although the association between skilled, trained staff and quality of care is well-established in research, how best to engage learners from an increasingly diverse workforce is less well understood. This paper outlines the context, framework, methods, and preliminary evaluation of the program. Data from participant surveys, interviews, and field notes suggest that program content and delivery positively impacted participants. Four major themes emerged: Enabling engagement through experiential learning; Valuing reciprocity in long-term care training; Creating meaningful change through significant learning ; and, Fostering sustained practice change through leadership involvement . The paper concludes with implications for LTC workforce training.